PENGARUH LEARNING START WITH A QUESTION (LSQ) TERHADAP BERPIKIR ANALISIS SISWA PADA MATERI SISTEM SARAF - Refirman Refirman; Sabrina Hasanah; Nurmasari Sartono (Universitas Negeri Jakarta, 2016)
Analytical thinking skills needed for students in solving problems encountered when learning topic are quite difficult and requires analysis of the issue. Learn to use Learning Start with a Question (LSQ) can help optimize student’s analytical thinking skills. Learning Start with a Question (LSQ) involving active students to seek out and study topic that will be taught. Students learn to solve their own problems in groups and cooperate with each other. Nervous system topic requires analysis of the relationship between the constituent organ tissue structure and associate them with the mechanisms and function disorders that occur in the nervous system topic. This study aimed to determine about effect of Learning Start with a Question (LSQ) on student’s analytical thinking in nervous system topic. The research was conducted in SMAN 33 Jakarta on March 2016. The reseach method used was a quasi experiment with Post Test Only Control Group Design. Subjects in this research were XI IPA 3 as experimental class and XI IPA 4 as control class. A total sample of 64 student was selected by simple random sampling technique. The instrumen used analytical thinking test was essay. Based the calculation, the average value of the test thinking analysis of the experimental class is 84 and the average value of the test thinking analysis of the control class is 82. Based on calculation, prerequisite test analysis data obtained was not normally distributes but homogeneous. The statistical hypothesis with Mann-Whitney test result on accepted null hypothesis at α 0,05. It showed that there was no about effect of Learning Start with a Question (LSQ) on student’s analytical thinking in nervous system topic.